Intestinal dysbiosis: Correlation with current chronic diseases and nutritional intervention (Research, Society and Development, 2019)
Intestinal dysbiosis is characterized by imbalance in relation to the proportion of favorable and unfavorable bacteria in the intestinal environment. The presence of diseases, poorly planned diets, drug conducts and environmental toxic exposure are associated with their greater expression. Thus, the objective of this bibliographic review was to present the main implications related to intestinal dysbiosis, its correlation with current diseases with a focus on promoting the design of nutritional strategies. Within this context, numerous factors contribute to the development of the condition, thus reinforcing the need for changes in lifestyle and promotion of dietary guidelines guided by the supply of probiotics and prebiotics in the control of this dysfunction.